Patient’s Perception of Safety in the Hospital Settings: A Qualitative Systematic Review - Dabaghi, Sahar; Zandi, Mitra; Abbaszadeh, Abbas; Ebadi, Abbas (Advances in Nursing & Midwifery, 2022)
Introduction: Patient safety is a key indicator and element in securing quality healthcare and this goal is multi-step, systemic, and multidisciplinary. The aim of the study was to investigate the meanings and definitions of “feeling of safety” in patient’s view and experiences during their hospital stay and to identify the antecedents and consequences of the concept. Methods: This qualitative systematic review was carried out based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2009. Six databases (PubMed, Web of Science, Scopus, ProQuest, Embase, Cochrane) were searched up to 2019 with no time and language limit. Two authors individually evaluated the study quality using Joanna Briggs Institute Qualitative Assessment and Review Instrument (JBI-QARI). Data from studies meeting the inclusion criteria were analyzed with concept analysis using of Walker and Avant approach (2011). Results: Twenty-five papers were included in this study. Data analysis resulted finally in eleven main categories: “receiving safe care”, “appropriate physical environment”, “resorting to spirituality”, “having previous negative experiences”, and “presence of family and friends”, “Feeling of Protection in a Safe Place”, “Emotional Enrichment and Confidence”, “Comfort and Tranquility”, “Feeling of Control on the Situation”, “Optimism towards Life” and “Coping”. Conclusions: Safe care is one of the fundamental needs in creating feeling of safety in patients. Focusing on this type of patient-centered care may promote quality care and improve the treatments provided in the hospital setting.